Dinamika Islamic Human Development Index, ketenagakerjaan, dan kemiskinan: Peran pertumbuhan ekonomi di Kabupaten Kebumen - Nurhidayah, Adelia Putri; Atieq, Muhammad Qoes (Nur Science Institute, 2025)
The purpose of this research is to examine the influence of the Islamic Human Development Index (I-HDI), Labour Force Participation Rate (LFPR), and Open Unemployment Rate (OUR) on poverty in Kebumen Regency during the period 2014-2024, with economic growth as a mediating variable. A quantitative approach was applied in this research. The analytical methods employed are path analysis and the Sobel test, utilising secondary data from official publications of the Central Statistics Agency, specifically those of the Kebumen District and the Central Java Province. The results show that the I-HDI has a significant positive impact on economic growth, while the LFPR has no significant impact; however, the OUR indicates a significant negative impact on economic growth. Furthermore, I-HDI was proven to have a positive and significant effect on poverty. In contrast, LFPR, OUR, and economic growth showed a significant adverse effect on poverty. In terms of indirect effects, economic growth was found to be effective in mediating the impact of I-HDI on poverty, but not in mediating the effects of LFPR and OUR on poverty.